Day-care patients and inpatients have similar visual acuity - Kartadinata, Erlani (Universa Medicina, 2011)
Cataract is a cause of avoidable blindness and its prevalence increases with age. Cataract surgery is the only possible therapeutic modality for improving visual function in cataract patients. The rising numbers of cataract patients require a type of cataract surgery with minimal side effects and without hospitalization. In this connection the day care cataract surgery has been introduced, with excellent results. Therefore the aim of the present study was to compare the visual acuity of day-care patients and inpatients after extracapsular cataract extraction (ECCE). A comparative observational study was carried out on 30 mature senile cataract patients with regard to type of care after ECCE surgery. The study subjects were allocated to two groups of 15 subjects each, i.e. the day-care group and the in-patient group. The patients were observed postoperatively on the first day, first week, fourth week, and eighth week. They subsequently were corrected for best visual acuity. Hypothesis testing was done using independent t-test and the Mann-Whitney test. The study results indicated that the visual acuity of the subjects after the eighth postoperative week did not differ significantly between both groups (p>0.05). There was no significant difference in outcome or risk of postoperative complications between day care and in-patient cataract surgery.This study therefore presents evidence that both post-ECCE day-care as well as post-ECCE inpatients had similar visual acuity levels.